2017
DOI: 10.1016/j.physd.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Invariant manifolds and the parameterization method in coupled energy harvesting piezoelectric oscillators

Abstract: Energy harvesting systems based on oscillators aim to capture energy from mechanical oscillations and convert it into electrical energy. Widely extended are those based on piezoelectric materials, whose dynamics are Hamiltonian submitted to different sources of dissipation: damping and coupling. These dissipations bring the system to low energy regimes, which is not desired in long term as it diminishes the absorbed energy. To avoid or to minimize such situations, we propose that the coupling of two oscillator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…Other geometric methods have been applied in [16,28,33,38,51,67,75,95]. These geometric methods also work for systems with magnetic fields [73] and for dissipative systems [61].…”
Section: Related Workmentioning
confidence: 99%
“…Other geometric methods have been applied in [16,28,33,38,51,67,75,95]. These geometric methods also work for systems with magnetic fields [73] and for dissipative systems [61].…”
Section: Related Workmentioning
confidence: 99%
“…Of course, the abundance of the hypotheses and the methods to check them are different in the Hamiltonian systems from the non-Hamiltonian ones. An interesting class of systems is that of non-Hamiltonian perturbations of Hamiltonian systems [38,34].…”
Section: Remarks On the Distinction Between 'A-priori Stable' And 'A-mentioning
confidence: 99%
“…There are several mechanisms of Arnold diffusion based on NHIM's. Since NHIM's exist even in non-Hamiltonian systems, these mechanisms apply to more general systems (e.g., magnetic fields [44] or dissipative systems [38]). The mechanisms based on NHIM's can accommodate also general time-dependent perturbations (e.g., quasiperiodic [19], or time-recurrent [32]).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al concluded that their system design allows for an almost 35-fold increase in energy harvesting compared to a conventional method. There are also solutions where the movement of two flexible beams is coupled via a spring [38]. Another concept for energy harvesting is presented in [39], where two beams with glued transducers are inertially coupled, as a result of which piezoelectrics are affected by components resulting from bending of beams and fluctuations of the inertial coupling mass.…”
Section: Introductionmentioning
confidence: 99%